2001
DOI: 10.1590/s1516-35982001000800014
|View full text |Cite
|
Sign up to set email alerts
|

Aminoácidos Digestíveis Verdadeiros do Milheto, do Milho e Subprodutos do Milho, Determinados com Galos Adultos Cecectomizados

Abstract: RESUMO -Os coeficientes de digestibilidade e o conteúdo de aminoácidos digestíveis verdadeiros do milho e seus subprodutos e do milheto foram determinados utilizando-se galos cecectomizados, em que 11 alimentos testados foram fornecidos a seis galos (15 g pela manhã e 15 g à tarde, após jejum de 24 horas) e seis galos foram mantidos em jejum para determinação das perdas endógenas. Após obtidos os coeficientes de digestibilidade e calculados os aminoácidos digestíveis, ajustaram-se equações para predizer a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
3
1
4
Order By: Relevance
“…The differences in the composition of the feedstuffs can also interfere in the digestibility coefficients of the nutrients, e.g., in the case of the meat and bone meal, in which there is no standardization during the processing to its obtainment, thus leading to variations mainly in the content of mineral matter and protein; Johnson et al (1998) elevated contents of ash cause decrease in the amount of protein, decreasing the levels of essential amino acids per unit of protein, without affecting its quality. The pearl millet presented different true digestibility coefficients of essential amino acids from the two varieties assessed by Rodrigues et al (2001a), like Rostagno et al (2005), who showed different values, except for arginine, which presented value similar to that of the present study. These differences can be related to the fiber content of the feedstuff, once the neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents were different between the feedstuffs; for the pearl millet evaluated in the present study, the NDF was 267.2 g/kg, and ADF was 38.1 g/kg; for the two varieties evaluated by Rodrigues et al (2001b), they were equal to 175.8 g/kg and 210.8 g/kg NDF; 76.5 g/kg and 100.3 g/kg ADF; and by Rostagno et al (2005), 193.3 g/kg NDF and 96.6 g/kg ADF.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The differences in the composition of the feedstuffs can also interfere in the digestibility coefficients of the nutrients, e.g., in the case of the meat and bone meal, in which there is no standardization during the processing to its obtainment, thus leading to variations mainly in the content of mineral matter and protein; Johnson et al (1998) elevated contents of ash cause decrease in the amount of protein, decreasing the levels of essential amino acids per unit of protein, without affecting its quality. The pearl millet presented different true digestibility coefficients of essential amino acids from the two varieties assessed by Rodrigues et al (2001a), like Rostagno et al (2005), who showed different values, except for arginine, which presented value similar to that of the present study. These differences can be related to the fiber content of the feedstuff, once the neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents were different between the feedstuffs; for the pearl millet evaluated in the present study, the NDF was 267.2 g/kg, and ADF was 38.1 g/kg; for the two varieties evaluated by Rodrigues et al (2001b), they were equal to 175.8 g/kg and 210.8 g/kg NDF; 76.5 g/kg and 100.3 g/kg ADF; and by Rostagno et al (2005), 193.3 g/kg NDF and 96.6 g/kg ADF.…”
Section: Resultssupporting
confidence: 83%
“…The true digestibility coefficients of the non-essential amino acids, in turn, were inferior, except for alanine, which was higher than the values found by that author. The true digestibility coefficients of the essential amino acids were also inferior to the values found by Rodrigues et al (2001a).…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…O milheto grão vem sendo testado como fonte alternativa de alimento para suínos (ADEOLA & ORBAN, 1995;BANDEIRA et al, 1996;BASTOS et al, 2002;BASTOS et al, 2005) e aves (RODRIGUES et al, 2001). Isso tem ocorrido em função do bom desenvolvimento do milheto em condições adversas de clima e solo brasileiros, o que levou ao aumento de áreas ocupadas com esta cultura.…”
Section: Introductionunclassified